Evaluation of T3, T4, TSH and Detection of Antithyroglobulin Antibodies Tg-Ab in Recurrent Miscarriage Women, Iraq - Al-Shihmany , Maha Radhi; R.S.AL-Attabi , Mohammed (American Journal of Biology and Natural Sciences, 2025)
There are many studies on the effect of thyroid diseases on the female reproductive system, but there is a lack of data that clarify the relationship between hypothyroidism and recurrent miscarriage, especially in the first three months of pregnancy. Therefore, this study aims to verify the existence of a definite relationship between recurrent miscarriage and maternal hypothyroidism. Thyroid function was evaluated by measuring the levels of thyroid hormones T3, T4, and TSH. The presence of thyroid autoimmune diseases was verified by searching for the presence of antibodies to thyroglobulin A-b. Blood samples were taken from recurrent miscarriage women (RMW) during the first trimester and from control (normal pregnant women). Thyroid hormones and Tg-Ab were tested by the ELISA technique. Results of the current study show a highly significant increase in Tg-Ab (P ≤ 0.05) in recurrent miscarriage compared to control, and percentages reach 144.06 ± 47.42 and 82.77 ± 7.84, respectively. But thyroid hormones T3, T4, and TSH were highly significant decreases (P ≤ 0.05) in recurrent miscarriage; the percentages reached 1.509 ± 1.36, 3.864 ± 1.08, and 1.098 ± 0.18 and reached 9.573 ± 2.13, 9.541 ± 2.53, and 4.090 ± 0.83, respectively, in RMW and control groups, respectively. This study concluded a relationship between changes in the levels of thyroid hormones T3 and T4 and thyroid-stimulating hormone, that they decreased significantly in women with recurrent miscarriages and the thyroglobulin antibodies increased clearly in the serum of women with recurrent miscarriages comparing to control.